2018
DOI: 10.1021/acs.chemrestox.8b00146
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos: Modern Insights for Toxicology in the Era of Engineered Nanomaterials

Abstract: Asbestos fibers are naturally occurring silicates that have been extensively used in the past, including house construction, but because of their toxicity, their use has been banned in 63 countries. Despite this, more than one million metric tons of asbestos are still consumed annually in countries where asbestos use has not been banned. Asbestos-related disease incidence is still increasing in several countries, including those countries that banned the use of asbestos more than 30 years ago. We highlight her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 156 publications
0
21
0
Order By: Relevance
“…Asbestos-induced mesothelioma remains a global health challenge (Carbone et al, 2019; Felley-Bosco and Macfarlane, 2018). While asbestos fibers have been causally linked to pleural mesothelioma (Wagner et al, 1962), the transformative mechanism and the exact cell of origin await clarification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asbestos-induced mesothelioma remains a global health challenge (Carbone et al, 2019; Felley-Bosco and Macfarlane, 2018). While asbestos fibers have been causally linked to pleural mesothelioma (Wagner et al, 1962), the transformative mechanism and the exact cell of origin await clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Compromised integrity of the adult mesothelium can result in pathologies including intra-abdominal organ adhesion (Tsai et al, 2018), serosal fibrosis (Mutsaers et al, 2015), pericarditis (Chiabrando et al, 2020), and mesothelioma tumors (Carbone et al, 2019; Yap et al, 2017). Malignant mesothelioma is a rapidly fatal solid tumor that can arise within the visceral or parietal mesothelia, predominantly as the result of environmental exposure to asbestos (Carbone et al, 2019; Felley-Bosco and Macfarlane, 2018; Odgerel et al, 2017; Wagner et al, 1962; Yap et al, 2017). While mesothelioma cases are increasing globally despite regulatory means to curb the use of causative agents, treatment remains limited (Hinz and Heasley, 2019; Yap et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been recently found that high-aspect ratio "long-bres" such as CNTs that are biopersistent pose an asbestos-like hazard. 43,44 The cytotoxicity of BNNT-1 was also shown to be cell-line dependent, as different cell lines reacted differently to BNNT-1 exposure. Of particular note was that NB4, being the only suspension cell line, exhibited the highest sensitivity to BNNTs of all the cell lines tested.…”
Section: Bnnt-1 and S-bnnt-1 Cytotoxicity Analyzed By Wst-8 Assaymentioning
confidence: 99%
“…Many studies have demonstrated that amphiboles are highly carcinogenic compared with chrysotile fibres. 1,3 While most inhaled asbestos fibres are eliminated by mucociliary clearance and alveolar macrophages (AM), the longer fibres (>10-20 µm) cannot be eliminated and result in chronic AM activation and "frustrated phagocytosis".…”
Section: Introductionmentioning
confidence: 99%
“…ROS play a pivotal role in asbestos toxicity. 3,[10][11][12] Reduction of O 2 by a single electron generates superoxide anion (O 2…”
Section: Introductionmentioning
confidence: 99%